Rancang Bangun Aplikasi Produk Ulew Coffee Berbasis Android - Kristianti, Novera; Putri, Jesica Paskaria (Journal of Information Technology and Computer Science, 2021)
Various kinds of business fields that are currently experiencing development, coffee shops are one of them. In addition to providing attractive packaging, business actors also need a good marketing strategy to develop existing businesses. This system is designed as a development of information media that has been run in several coffee shops, namely information media in the form of pamphlets, brochures, catalogs, advertisements in newspapers and on the radio. Because it is considered less than optimal, a product sales application will be developed at the coffee shop. With the availability of services through android, visitors can find out information about the product.Because of the above problems created an innovation to create an Android-based application that most people certainly have a smartphone with an Android operating system. The software development method used is Waterfall with several stages, namely requirements analysis, system design, implementation, integration and testing as well as operation and maintenance. Making the system using Visual Studio Code and Android Studio using the Software Development Kit, namely Flutter. The programming language uses Dart and PHP. This application contains product availability information where data will be entered through an online system so that information about the product can be seen by Ulew Coffee and consumers.